2020
DOI: 10.1002/jbt.22619
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of panaxydol against repeated administration of aristolochic acid on renal function and lipid peroxidation products via activating Keap1‐Nrf2/ARE pathway in rat kidney

Abstract: Panaxydol (PX), a polyacetylenic compound isolated from the roots of Panax notoginseng, is found to possess various biological functions. However, its protective effects against aristolochic acid (AA)‐induced renal injury have not been elucidated yet. The present study was undertaken to elucidate the renoprotective effect of PX on Wistar male rats via activating Keap1‐Nrf2/ARE pathway. Experimental animals were randomized into four groups, such as control group, I/R group, AA (5 mg/kg/d; ip for 10 days), and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Finally, lipid peroxidation, one of the final responses of oxidation in CKD [ 40 , 41 ], was studied by staining for 4-HNE. A significant increase of lipid peroxidation was only observed in the kidneys of 18-month-old mice, but not at 12-months-old ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, lipid peroxidation, one of the final responses of oxidation in CKD [ 40 , 41 ], was studied by staining for 4-HNE. A significant increase of lipid peroxidation was only observed in the kidneys of 18-month-old mice, but not at 12-months-old ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, NRF2 activation goes beyond cytoprotective properties, as it is implicated in lipid metabolism [ 67 ]. In CKD, aberrant quantities of plasma lipids are a target of ROS, creating subproducts such as 4-HNE, among others [ 40 ]. In our study, we only observed 4-HNE production at 18 months, suggesting an excess of ROS production and lipid deposition, not compensated by efficient antioxidant responses, as evidenced by low Cat and Sod-1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the degree of lung injury in mice pretreated with the ferroptosis inhibitor ferrostatin-1 was significantly improved, suggesting that ferroptosis plays an important role in the occurrence and development of ALI caused by MTB and LPS [51,52]. In addition, panaxydol can inhibit ferroptosis in ALI induced by LPS, and its effect is due to the upregulation of the Kelch-like ECH-associated protein 1 (Keap1)-Nrf2/heme oxygenase-1 (HO-1) pathway [53,54]. Pseudomonas aeruginosa is an important pathogen that causes nosocomial infection.…”
Section: Infection-related Alimentioning
confidence: 99%
“…The major characteristics of extensive tubulointerstitial fibrosis and the scar formation accompanied by renal tubular atrophy have been found in mouse and human AAN [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Recent studies have revealed that AAI causes severe a reduction in the capillaries around the renal tubules, leading to hypoxia and the death of the renal tubular epithelial cells [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Furthermore, AAI increased the expression of fibrotic cytokine transforming growth factor 1 (TGF-1) and connective tissue growth factor (CTGF), which enhance fibrosis and scar formation [ 5 , 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%